Floristic, life form, and chorological studies of unharvested beech (Fagus orientalis Lipsky) site in Zilaki forest, Guilan (مجله جنگل ایران, 2014)
The study area with 170 hectares is located in the north of Rudbar and between 1010-1560 m a.s.l. There is not any harvesting in the study area due to a lack of a road network. This research has been carried out to identify the floristic composition, life forms and chorology of all plants in this area. The final results of the studies on floras showed that 47 plant species belonged to 46 genera and 37 families. The dicots with 34 taxa were the richest group of flora followed by monocots with 7 taxa, and Pteridophytes with 6 taxa. Dominant life forms include geophytes (49%), followed by phanerophytes (23.4%). From the chorological point of view, the largest proportion of the flora belongs to the Euro-Siberian elements (42.6%) followed by Pluriregional elements (14.9%), Euro-Sibirian/ Mediterranean/ Irano-Turanian and Euro-Sibirian/ Mediterranean (10.6%).